EFFECT OF POLYMER PROSTHETIC CONSTRUCTION TREATED WITH GLOW-DISCHARGE PLASMA ON ORAL MUCOSA (CLINICAL CASE) - E. O. Kudasova; E. V. Kochurova; T. M. Vasilieva; M. V. Nekludova; V. A. Myasnikov; Aung Myat Hein (Опухоли головы и шеи, 2017)
Prosthetic material should induce minimal pathological reaction when in contact with the oral mucosa, especially during oral rehabilitation of patients with tumors of the oral mucosa. The article presents monitoring of a patient after surgery for cancer of the buccal mucosa at the stage of orthopedic rehabilitation. Treatment plan proposed complex oral rehabilitation. A maxillary complete removable denture was manufactured as well as metalloceramic and partial mandibular dentures. Plasma chemical modification of the removable dentures was planned after correction of the prosthetics and primary adaptation. Removable dentures were applied at the maxilla and mandibula. Per our recommendations, the patient was examined weekly for a month and monthly for 6 months. No new tumors or pathological elements were observed.Conclusions. Changes in critical surface tension of the removable dentures made of acrylic plastic improve their biological characteristics as demonstrated by positive clinical dynamics. Prosthetic constructions with hydrophilic surface are recommended in complex clinical cases when patients with tumors of the oral mucosa require dentures.